An observational study of febrile seizures: the importance of viral infection and immunization. Issue 1 (December 2016) - Francis, Joshua; Richmond, Peter; Robins, Christine; Lindsay, Katie; Levy, Avram; Effler, Paul; Borland, Meredith; Blyth, Christopher
Abstract Background Febrile seizures are common in young children. Annual peaks in incidence mirror increased respiratory virus activity during winter. Limited virological data are available using modern diagnostic techniques for children with febrile seizures. We aimed to determine the frequency of detection of specific viral pathogens in children with febrile seizures, to describe risk factors including recent vaccination and clinical features associated with specific etiologies. Methods An observational study was performed. Children aged 6 months to 5 years presenting to the Emergency Department of a tertiary children's hospital in Western Australia with febrile seizures were enrolled between March 2012 and October 2013. Demographic, clinical data and vaccination history were collected, and virological testing was performed on per-nasal and per-rectal samples. Results One hundred fifty one patients (72 female; median age 1.7y; range 6 m-4y9m) were enrolled. Virological testing was completed for 143/151 (95%). At least one virus was detected in 102/143 patients (71%). The most commonly identified were rhinoviruses (31/143, 22%), adenovirus (30/151, 21%), enteroviruses, (28/143, 20%), influenza (19/143, 13%) and HHV6 (17/143, 12%). More than one virus was found in 48/143 (34%). No significant clinical differences were observed when children with a pathogen identified were compared with those with no pathogen detected. Febrile seizures occurred within 14 days of vaccine administration in 16/151 (11%). Conclusion At least one virus was detected in over two thirds of cases tested (commonly picornaviruses, adenovirus and influenza). Viral co-infections were frequently identified. Febrile seizures occurred infrequently following immunization.